Synthesis and characterization of GdVO4 nanostructures by a tartaric acid-assisted sol-gel method - Chumha N. (2014)
GdVO4 nanoparticles were prepared by a sol-gel method employing tartaric acid as a chelating agent. Effects of calcination temperature and mole ratio of total metal ions to tartaric acid on the products were investigated. The products, characterized by XRD, FESEM and TEM, were tetragonal GdVO4 nanoparticles with diameters of about 20-30nm. TG and DSC data showed weight loss and phase formation due to evaporation and decomposition processes. FTIR presented the stretching band of VO43- tetrahedrons and Raman analysis revealed the vibrational modes of the GdVO4. © 2014 Elsevier Ltd and Techna Group S.r.l.